Association Between Chronic Osteomyelitis and Risk of End-Stage Renal Disease. Issue 27 (July 2015) - Lin, Shih-Yi; Lin, Cheng-Li; Tseng, Chun-Hung; Chang, Yen-Jung; Wang, I-Kuan; Yeh, Hung-Chieh; Kao, Chia-Hung; Nadasdy., Tibor
<x xml:space="preserve">Abstract</x> Abstract Inflammation, which initiates endothelial dysfunction, vascular atherosclerosis, and oxidative stress, may negatively influence renal function and accelerate the development of end-stage renal disease (ESRD). The role of chronic osteomyelitis (COM), a chronic inflammatory disease, in the development of ESRD has not been investigated. This study explored whether patients with COM have a higher risk of ESRD than that of patients without COM. Taiwan National Health Insurance claims from 1997 to 2010 were used to identify 24, 267 newly diagnosed patients with COM and 97, 068 age- and sex-matched non-COM controls for comparison. The risks of ESRD among COM patients, with adjustment for comorbidities, namely, hypertension, diabetes, coronary artery disease, congestive heart failure, and hyperlipidemia, were assessed until the end of 2010. ESRD risk was 2.01-fold higher (95% confidence interval [CI]: 1.81–2.25) in the COM cohort than in the non-COM cohort. Regarding the joint effect of COM with comorbidity, the ESRD risk was 1.57-fold higher (95% CI: 1.23–2.00) for the COM cohort without comorbidities and increased to 2.25 (95% CI: 1.97–2.57) for the COM cohort with at least 1 comorbidity. Age-specific analysis revealed that the adjusted ESRD risk for the COM cohort increased as age decreased, with the highest hazard ratio being 17.8 (95% CI: 5.18–61.4) for patients aged 20–34 years. This was the first study to report that COM is associated with an increased risk of ESRD, particularly among patients with comorbidities and younger patients.